The Carmelites and antiquity Mendicants and their pasts in the Middle Ages - Jotischky, Andrew, 1965- (Oxford University Press, 2002)
This study of Carmelite legends examines the circumstances under which their traditions were constructed, describes the evolution of the traditions themselves from the 13th to the 16th century and places them within the wider context of historical writing by religious orders.